The Analysis Of The Effect Of Profitability, Leverage, And Sales Growth Toward Tax Avoidance In Consumer Goods Companies Listed On The Indonesia Stock Exchange - Jefri Tanika; Yenni Martok (Journal of Accounting and Management Innovation, 2022)
The goal of this study is to determine whether profitability, leverage, and sales growth have a partial or simultaneous significant effect on tax avoidance in consumer goods companies listed on the Indonesian Stock Exchange. This study examines three independent variables: profitability, leverage, and sales growth. However, the percentage of tax avoidance is the dependent variable in the research. This study employs a quantitative technique based on secondary data and purposive sampling, with a total of 88 samples selected over a two-year period among 228 Indonesian stock exchange-listed consumer goods sector businesses. SPSS 26 was used to perform multiple linear regression and hypothesis testing in this investigation. The following is the outcome of this research. Profitability has a significant effect in tax avoidance for consumer goods companies listed on the Indonesian Stock Exchange. Leverage has no significant effect on tax avoidance in consumer goods companies listed on the Indonesian Stock Exchange. In consumer goods sector companies registered on the Indonesia Stock Exchange, sales growth has no significant effect on tax avoidance. Profitability, leverage, and sales growth all have no simultaneous effect on tax avoidance in consumer goods companies listed on the Indonesian Stock Exchange.